The genome survey of male and female Hapalogenys analis - Liu, Kai; Qu, Yin-Quan; Shi, Hui-Lai; Ping, Hong-Ling; Gao, Tian-Xiang (Frontiers in Marine Science, 2024)
Effectively assessing the basic genomic information of a species is fundamental for conducting molecular research and provides a foundation for constructing whole-genome maps. Hapalogenys analis is a temperate and tropical nearshore marine fish in China’s coastal waters, with significant economic value and high aquaculture potential. However, the genomic differences between male and female individuals of this species are not yet apparent. This study conducted whole-genome survey analyses on male and female H. analis to provide basic genomic information. According to K-mer analysis, the genome sizes of female and male fish were 436.24 Mb and 493.21 Mb. The heterozygosity rates were 0.58% for females and 0.23% for males. The proportion of repetitive sequences of female and male fish were 42.95% and 51.20%. The GC content of the genomes was 43.30% for female and 43.20% for male. The sizes of the assembled genomes were 589.18 Mb for female and 592.02 Mb for male, with N50 lengths of 3,135 bp and 3,041 bp, respectively. SSR screening results showed that 959,447 and 894,158 SSR sequences were detected in the genomes of female and male, respectively. The lengths of the assembled mitochondrial genome sequences were 19,755 bp for female and 19,754 bp for male, each containing 38 genes. Among these mitochondrial sequences, 13 protein-coding genes were identified, including 7 NADH dehydrogenase, 3 cytochrome c oxidase, 1 cytochrome b, and 2 ATP synthase genes. Both sequences contained 23 tRNA genes and 2 rRNA genes. This study provides a theoretical basis for constructing a high-quality whole genome of H. analis and valuable data for subsequent molecular breeding research.